The Relationship between Mobile Phone Usage and Academic Performance of Secondary School Students: A Case Study in Asian International School - Wedikandage, L.N.P.; Zahir, M.R. (International Journal of Research and Innovation in Social Science, 2024)
Technology is a global imperative because of its contributions to human existence and has improved global socioeconomic relations. As a result, the mobile phone has become the most important mode of communication today. It is also an important learning tool for today’s school students. It enables students to access online learning platforms, course resources, and interact digitally. The goal of this study was to determine the relationship between mobile phone usage and academic performance of secondary level students at an international school in Sri Lanka. The study’s sample consisted of 523 Secondary level students from an International School, ranging from Form 1 to Upper 6. For the study, a survey research design and questionnaires were used. Google Forms was used to create the students’ survey. The findings show that there is a positive relationship between mobile phone usage and academic performance among secondary school students, no relationship between mobile phone usage and academic performance among secondary school students of different parents’ occupations, and a relationship between the frequency of mobile phone usage and academic performance among secondary school students.
Keywords: Mobile Phone; Academic performance; secondary level; International schools